Effects of melatonin, vitamin E and octreotide on lipid peroxidation during ischemia-reperfusion in the guinea pig retina - Çelebi, S; Dilsiz, N; Yilmaz, T; Kükner, AS (Wichtig Editore, 2002)
PURPOSE. The purpose of this study is to provide evidence that free radical damage is a component of retinal ischemia-reperfusion (I/R) injury, and to determine whether melatonin, vitamin E and octreotide can protect the retina from this injury. METHODS. The right eyes of 50 male guinea pigs weighing 500-600 g were used. The animals were randomly assigned to group 1 (control), group 2 (I/R), group 3 (melatonin + I/R), group 4 (vitamin E + I/R) and group 5 (octreotide + I/R). Groups 3, 4 and 5 received four subcutaneous injections with a 6-h interval for a total daily dose of 10 mg/kg melatonin, 150 mg/kg vitamin E and 22 mg/kg octreotide. The first dose of each substance was administered 5 minutes before retinal ischemia, which was induced for 1.5 hours, followed by reperfusion for 24 hours. All three substances were repeated for 6, 12 and 18 hours during reperfusion. The animals were killed at 24 hours of reperfusion. Retinas were isolated and processed for the quantification of malondialdehyde (MDA). RESULTS. The compounds had the following relationships: melatonin more than vitamin E more than octreotide in preventing retinal damage by ischemia-reperfusion. All three gave significant protection against the formation of MDA (10.4 +/- 2.3, 12.4 +/- 2.4, 13.9 +/- 1.5 nmol/100 mg tissue wet weight, respectively) compared to the control (3.7 +/- 1.3 nmol/100 mg tissue wet weight) and I/R groups (22.7 +/- 6.2 nmol/100 mg tissue wet weight). CONCLUSIONS. This study demonstrates the inhibitory effect of melatonin, vitamin E and octreotide on MDA levels during retinal ischemia-reperfusion injury.
34th National Ophthalmology Congress -- SEP 30-OCT 04, 2000 -- ANTALYA, TURKEY
Keywords: guinea pig; retina; ischemia-reperfusion injury; melatonin; vitamin E; octreotide; malondialdehyde